Politics and Demographics in Poland - Kwiek, Marek (International Higher Education, 2011)
The article discusses the impact of changing demographics on the future of private higher education in Poland in the context of ongoing higher education reforms. After two decades of massive demand-absorbing growth, Polish higher education is expected to enroll 30-40% less students in 2022 due to demographic decline already felt throughout the system. Consequences for the private sector and policy options for the state are discussed.